2017
DOI: 10.1002/cbin.10727
|View full text |Cite
|
Sign up to set email alerts
|

β‐carotene treatment alters the cellular death process in oxidative stress‐induced K562 cells

Abstract: Oxidizing agents (e.g., H O ) cause structural and functional disruptions of molecules by affecting lipids, proteins, and nucleic acids. As a result, cellular mechanisms related to disrupted macro molecules are affected and cell death is induced. Oxidative damage can be prevented at a certain point by antioxidants or the damage can be reversed. In this work, we studied the cellular response against oxidative stress induced by H O and antioxidant-oxidant (β-carotene-H O ) interactions in terms of time, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…β-Carotene is a chemical compound of the family of terpenes; β-carotene is the most abundant carotenoid in nature, and it is the most important pro-vitamin in the human diet [ 154 ]. The mucosa of the small intestine transforms it into vitamin A, and it is then stored in the liver as a retinol ester [ 155 ]. As a lipo-soluble antioxidant, it reduces the chances of heart attacks and increases the efficiency of the immune system [ 155 ].…”
Section: Adverse Effects Of Antioxidant Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Carotene is a chemical compound of the family of terpenes; β-carotene is the most abundant carotenoid in nature, and it is the most important pro-vitamin in the human diet [ 154 ]. The mucosa of the small intestine transforms it into vitamin A, and it is then stored in the liver as a retinol ester [ 155 ]. As a lipo-soluble antioxidant, it reduces the chances of heart attacks and increases the efficiency of the immune system [ 155 ].…”
Section: Adverse Effects Of Antioxidant Agentsmentioning
confidence: 99%
“…The mucosa of the small intestine transforms it into vitamin A, and it is then stored in the liver as a retinol ester [ 155 ]. As a lipo-soluble antioxidant, it reduces the chances of heart attacks and increases the efficiency of the immune system [ 155 ]. Low β-carotene consumption rates enhance systemic OS in MS patients [ 156 ].…”
Section: Adverse Effects Of Antioxidant Agentsmentioning
confidence: 99%
“…It benefits from an important component, NRF2 (Nuclear Factor Erythroid 2-Related Factor 2), which is a transcription factor and a member of the cap ‘n’ collar (CNC) subfamily of basic region leucine zipper (bZip) transcription factors. The key role of NRF2 in controlling cellular defense against environmental oxidant agents has been revealed by studies in which NRF2-knocked-out mice have been shown to exhibit sensitivity to hyperoxia-induced injury, as well as increased susceptibility to toxic xenobiotic, including carcinogens 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, β-carotene induced increase in ROS and caspase-3 activity that may reduce the level of DNA repair Ku proteins resulting in the apoptosis of AGS gastric cancer cells [ 128 ]. On the contrary, β-carotene pre-treatment exerted antioxidant effects against oxidative stress in K562 human erythromyeloblastoid leukemia cells protecting them against the damage by oxidative stress [ 129 ].…”
Section: The Use Of Carotenoids In Preclinical Cancer Researchmentioning
confidence: 99%